Study on the relationship between microbial composition within obstructive biliary stents and the severity of obstruction and duration of stent placement. - Ichiro Sugawara; Yosuke Kawahara; Lena Takayasu; Kimio Isshi; Masayuki Kato; Shingo Ono; Yuko Hara; Toshiki Futakuchi; Hiroto Furuhashi; Rina Kurokawa; Kazuki Sumiyama; Wataru Suda (PLoS ONE)
Biliary stent occlusion is due, in part, to biofilm formation by bacteria. However, previous culture-based approaches may not have revealed all microorganisms on the surface. Twenty-seven patients underwent endoscopic retrograde biliary drainage for the removal or replacement of plastic biliary stents. We analyzed occlusion severity using image-analyses of a longitudinal section of the biliary stent and evaluated the microbial profile of sludge deposition inside the stents using 16S rRNA sequencing with a MiSeq Illumina platform. We then evaluated the association of microbial profiles with the duration of stent placement and stent occlusion severity. Actinobacteria and Synergistetes were much more abundant in occluded stents compared with non-occluded stents. An abundance of Bifidobacterium spp. and OTU00006 Bifidobacterium animalis (100%) correlated with stent occlusion severity (rho, 0.62; p<0.001; and 0.42; p = 0.03, respectively), and this relationship remained after adjusting for the duration of stent placement (p = 0.03 and 0.05, respectively). The genus Bifidobacterium and Bifidobacterium animalis were associated with the degree of occlusion in plastic biliary stents.